Improving Teacher Competence Through Open Inquiry-Based Scientific Investigation Development Training - Haris, Abdul; Mahir, Mahir (Innovare Journal of Education, 2025)
This research aims to improve science teachers’ competence in formulating problems, determining investigation variables, drawing conclusions, interpreting tables, and interpreting graphs through training in developing open inquiry-based scientific investigations. The research design uses a quasi-experimental approach with pre-test and post-test to measure changes in competencies by Ten (10) teachers before and after participating in the training. The study showed a significant improvement in teachers’ skills after participating in the training. Teachers can better formulate investigation problems, determine relevant variables, draw the correct conclusions, and interpret data in tables and graphs. Despite the challenges in implementing the training, such as time and resource management, this training has proven to be effective in improving science teachers’ competence in designing and implementing open inquiry-based learning. This research contributes to developing teacher competencies in the future and scientific inquiry-based learning in Indonesia, which is expected to improve the quality of education and students’ critical thinking skills.